Physical, optical and gamma-ray shielding properties of BaO- La2O3-B2O3 and BaO-Na2O-B2O3 glass systems at 662 keV. (September 2019) - Siengsanoh, K; Hongtong, W; Chaiphaksa, W; Limkitjaroenporn, P; Kaewkhao, J
Abstract: In this work, glasses with composition xBaO : 20La2O3: (80-x)B2O3 and xBaO : 20Na2O3: (80-x)B2O3 (where x= 15, 20, 25 and 30 mol%) were prepared using melt-quenching method. Physical, optical and gamma-ray shielding properties were investigated and compared with theoretical calculations. 137 Cs was used as γ-source for investigating experimental mass attenuation coefficient at 662 keV energy. The theoretical mass attenuation coefficient was calculated using WinXcom program. The density and the molar volume show increasing trend with increase in BaO concentration. Transmission spectra shows dissimilarity in their transmittance for BaO-Na2O-B2O3 and BaO-La2O3-B2O3 glasses. BaO-Na2O-B2O3 glasses show higher transmittance in the visible region than compared to BaO-La2O3-B2O3 glasses. Mass attenuation coefficients, Zeff show increasing trend whereas HVL at 662 keV show decreasing trend with increase in BaO concentration for these both these glasses. Theoretical and experimental mass attenuation results are in good agreement with each other. The synthesized glasses show potential use for radiation shielding material applications.